"Low initial pre-hospital end-tidal carbon dioxide predicts inferior clinical outcomes in trauma patients". Issue 9 (September 2021) - Bryant, Mary Kate; Portelli Tremont, Jaclyn N; Patel, Zachary; Cook, Nicole; Udekwu, Pascal; Reid, Trista; Maine, Rebecca G; Moore, Scott M
Highlights: End-tidal CO2 is a non-invasive technology that can be easily obtained in the pre-hospital setting on non-intubated patients. Low pre-hospital end-tidal CO2 (<28.5 mmHg) associates with increased mortality risk in trauma patients. Trauma patients with low pre-hospital end-tidal CO2 (<28.5 mmHg) are at increased risk for needing blood product transfusions. Pre-hospital end-tidal CO2 has the potential to improve triage and resource mobilization for trauma patients. Abstract: Introduction: Current guidelines continue to lead to under- and over-triage of injured patients in the pre-hospital setting. End-tidal carbon dioxide (ETCO2) has been correlated with mortality and hemorrhagic shock in trauma patients. This study examines the correlation between ETCO2 and in-hospital outcomes among non-intubated patients in the pre-hospital setting. Methods: We retrospectively studied a cohort of non-intubated adult trauma patients with initial pre-hospital side-stream capnography-obtained ETCO2 presenting via ground transport from a single North Carolina EMS agency to a level one trauma center from January 2018 to December 2018. Using the Liu method, the optimal threshold for low ETCO2 was ≤ 28.5 mmHg. Results: Initial pre-hospital ETCO2 was recorded for 324 (22.0%) of 1473 patients with EMS data. Patients with low ETCO2 (N = 98, 30.3% of cohort) were older (median 58y vs 45y), but mechanisms of injury and scene vital signs were similar (p>0.05) between low and normal/high ETCO2 cohorts. Median injury severity score (ISS) did not differ significantly between the low and normal/high ETCO2 groups (5 vs 8, p=0.48). Compared to normal/high ETCO2, low ETCO2 correlated with increased unadjusted odds of mortality (OR 5.06), in-hospital complications (OR 2.06), and blood transfusion requirement (OR 3.05), p<0.05. Low ETCO2 was associated with 7.25 odds of mortality (95% CI 2.19, 23.97, p=0.001) and 3.94 odds of blood transfusion (95% CI 1.32-11.78) after adjusting for age, ISS, and scene GCS. All but one of the massive transfusion patients (N = 8/9) had a low pre-hospital ETCO2. Conclusions: Low initial pre-hospital ETCO2 associates with poor clinical outcomes despite similar ISS and mechanisms of injury. ETCO2 is a potentially useful pre-hospital point-of-care tool to aid triage of trauma patients as it may identify hemorrhaging patients and predict mortality.